A case of primary cryptococcosis of the lung - Oshikiri, Taro; Niizeki, Hiroto; Shiono, Tsuneo; Ootake, Setsuyuki; Yamaguchi, Jun; Takenouchi, Nobuo; Munemura, Tadanobu (Nihon Kokyuki Geka Gakkai zasshi (Kyoto, 1992), 1996)
A medical examination of a 52-year-old man revealed an abnormal shadow in the right upper lung field. He was thus admitted to our hospital. Chest CT scan revealed a solitary mass lesion (2 cm in size) in the S2 area with no contractile change or lymph node swelling. TV-brushing cytology showed no abnormal findings, and video-assisted partial resection of the right upper lobe was performed. Histologically, the lesion was confirmed as cryptococcosis of the lung. This case had no associated immuno-suppressive disorder (such as a malignant or a collagen disease) and no history of being a bird fancier. However, because he is a veterinarian, he was suspected of having had occupational exposure. The postoperative course was smooth, and there has been no sign of recurrence even though no adjuvant chemotherapy was administered.